Design of quality system documentation in hydrotiller production unit as improvement of quality management system in small and medium enterprise - Nilda Tri Putri, Nilda Tri Putri (Inderscience Enterprises Ltd., 2016)
CV Citra Dragon is one of small and medium industries producing equipment and agricultural machinery (also known as Alsintan) in West Sumatra, Indonesia. The company needs to implement a quality management system (QMS) to win the competition as a result of globalisation. QMS applied in that company is still limited to a single product that is rice thresher machine (thresher). Therefore, the scope of the QMS in the company needs to be extended to other products that are hydro tiller which is one of the two main products produced by it. The existence of a well-documented quality system is important for a company in implementing QMS. Therefore, it is necessary to design a quality system documents on the company related to hydro tiller production process. It is based on the ISO 9001: 2008. Quality systems documents are required and made in the study include three levels of documentation, the procedures, work instruction, and form.